The DNP by 2015: A Study of the Institutional, Political, and Professional Issues that Facilitate or Impede Establishing a Post-Baccalaureate Doctor of Nursing Practice Program - Auerbach, David I. (Rand Health Q, 2015)
In 2004, members of the American Association of Colleges of Nursing (AACN) voted to endorse a position statement identifying the doctor of nursing practice (DNP) degree as the most appropriate degree for advanced-practice registered nurses (APRNs) to enter practice. At the same time, AACN members voted to approve the position that all master's programs that educate APRNs to enter practice should transition to the DNP by 2015. While the number of DNP programs for APRNs has grown significantly and steadily over this period, at this time, not all nursing schools have made this transition. To better understand why, the AACN contracted with RAND to investigate schools’ progress toward this goal and the factors that facilitate or impede this transition. This article describes the results of a mixed-method RAND study undertaken between October 2013 and April 2014 that sought to understand schools’ program offerings to prepare APRNs to enter practice and the reasons for those offerings, as well as the barriers or facilitators to nursing schools’ full adoption of the DNP.